استخدام طريقة المحادثة لنجاح تعلم اللغة العربية بمعهد المنورة عيمفلاك عوديريجو ديويك جومبانج - Nurfaizi Zamzami; Abdul Qodir (JURNAL AL-IHDA : Media Ilmiah Bahasa Arab, 2023)
Arabic is a very important language to learn and requires a lot of time to learn it. Therefore, because learning Arabic is quite complicated, it is necessary to use various methods of learning Arabic so that learning Arabic can be carried out properly and conducively. One way that I use is to use the muhadasah or maharah kalam method. The muhatdasah method is a conversation between two or more people who are mutually reciprocal. In learning Arabic, Muhadatsah lessons are intended to facilitate communication skills (Maharah Kalam or Maharah Lughah) between one another. This Maharah Kalam is the essence of learning Arabic, being able to communicate both directly and indirectly using Arabic. The researcher used qualitative methods, therefore the researcher went down to the field and interviewed several sources. And why did I take the research location at Pondok Almunawaarah because Arabic is well known which is quite popular in the field of language. The results of scientific research show that the use of the conversational method is a success in learning Arabic at the Al-Munawwarah boarding school, ngeplak ngudirejo, diwek Jombang. daily conversations and supported by Arabic speaking teachers.